ECONOMIC TRANSFORMATION AND ENERGY CONSUMPTION TO REDUCE CARBON EMISSIONS TOWARDS INDONESIA'S SDGS - Sherly Anggiliana Puspitasari; Anik Sri Widawati (Jurnal Ilmiah Ekonomi Bisnis, 2025)
Indonesia’s carbon dioxide emissions continue to rise despite its emission reduction commitments, highlighting a gap between policy and implementation. The country’s reliance on fossil fuels, limited penetration of renewable energy, and the varied effects of foreign direct investment and industrialization highlight the importance of empirical analysis of the key drivers of emissions. This study strengthens the ARDL-based empirical evidence on the nexus among FDI, industrialization, energy consumption, and carbon emissions in Indonesia by incorporating the Environmental Kuznets Curve (EKC), the Pollution Haven Hypothesis, the Energy–Emissions Nexus Theory, and the Sustainable Development Theory. Using annual data from 1984 to 2023, the analysis evaluates the impacts of foreign direct investment, manufacturing value added, oil consumption, coal consumption, and low-carbon energy use on carbon dioxide emissions in both the short and long run. The results indicate that foreign direct investment initially increases emissions but has an insignificant adverse effect in the long run. Industrialization, oil, and coal consumption significantly raise emissions in both periods, while low-carbon energy consumption reduces emissions only in the long run. These findings suggest that Indonesia’s clean energy transition requires more substantial policy commitment, greater green investment, and improved industrial efficiency to achieve sustainable decarbonization.